TEACHERS’ PERCEPTION ON STUDENTS’ READING ACHIEVEMENT (A STUDY CONDUCTED AT SMP NEGERI 2 TONDANO) - Linda Pratiwi Bobihu; Rombepajung, Paula; Posumah, Jennie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
Reading becomes an aspect of acceptance to acquire knowledge. Learners get in-depth information by reading (text and context), so reading is very important for learners. The purpose of this research is to describe teachers' perceptions of English on students' reading achievement. This research was conducted at SMPN 2 Tondano. This research is a qualitative research with a descriptive research type. Data collection methods used in this study were interviews, observation, and documentation. The information obtained by the researcher came from several English teachers. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. Based on the results of the research, it shows that the success of learning to read students will greatly increase with the amount of vocabulary they have and understanding of reading material. Reading success can be achieved by applying it effectively, such as contextual learning, namely learning that is in line with the goal of being more communicative between students and teachers in adding insight. Therefore, there is a perception about the success of teaching students to read. Learning to read at SMPN 2 Tondano is perceived by teachers critically and in various ways. This varies in terms of the learning process, class situation, the media used, the environment outside the classroom, student motivation and interest as well as the vocabulary mastered. In reading success SMPN 2 Tondano students get different results because it is in accordance with the level of motivation, interest, and curiosity as well as understanding in studying a text.